Copolymer, ethylene copolymer composition, fuel cell gasket, and molding
By designing an ethylene-α-olefin-non-conjugated polymer, the problem of insufficient mechanical strength and fluidity of existing fuel cell seal materials under low temperature conditions is solved, and the high thermal stability and low compression coefficient of the material under high and low temperature conditions is achieved, which improves the overall performance of fuel cell seals.
Patent Information
- Application Number
- JP2023147906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
The existing fuel cell sealing materials lack mechanical strength and fluidity under low temperature conditions, and the silicone material has poor cooling performance at low temperatures, which affects the sealing performance.
A ethylene-α-olefin-non-conjugated polymer copolymer is used, which consists of ethylene [A1], α-olefin [A2] and non-conjugated polymer [A3], designed in specific structures and proportions to improve the low temperature performance and production efficiency of the material.
The high thermal stability, low compression coefficient and excellent low-temperature elastic recovery performance of the material under high and low temperature conditions are achieved, and the overall performance of fuel cell seals is improved.
Smart Images

Figure 2025040845000001 
Figure 2025040845000002 
Figure 2025040845000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer, an ethylene copolymer composition, a fuel cell gasket, and a molded article. [Background technology]
[0002] Ethylene-α-olefin copolymer elastomers, such as ethylene-propylene copolymers (EPM, EPR) and ethylene-propylene-diene copolymers (EPDM), do not have unsaturated bonds in the main chain of their molecular structure, and therefore have superior heat aging resistance, weather resistance, and ozone resistance compared to general-purpose conjugated diene rubbers. They are widely used in applications such as automotive parts, electric wire materials, electronic and electrical parts, building and civil engineering materials, and industrial parts.
[0003] It is known that a rubber molded article for sealing is obtained by using EPDM (for example, Patent Document 1). Seal packings, which are rubber molded articles for sealing, are used for various purposes such as automobiles, industrial machines, and electronic parts, but since automobiles and industrial machines are also used in cold regions, the seal packings are required to have low-temperature properties in addition to mechanical strength at room temperature.
[0004] Furthermore, Patent Document 2 proposes an ethylene copolymer composition for fuel cell gaskets capable of forming a seal packing that combines low-temperature properties and mechanical strength (strength and elongation), the composition containing an ethylene-α-olefin-non-conjugated polyene copolymer including a structural unit derived from ethylene [A] having a B value of 1.20 or more, a structural unit derived from an α-olefin [B] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [C]. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2000 / 59962 [Patent Document 2] JP 2017-075293 A Summary of the Invention [Problem to be solved by the invention]
[0006] For example, fuel cell gaskets for fuel cell vehicles (FCVs) are rubber parts that prevent leakage of hydrogen, oxygen, and water inside the FC stack, and require excellent durability in addition to low-temperature properties. In addition, there is a demand for compositions that can be used for fuel cell gaskets and the like that can improve fluidity and shorten vulcanization times to further improve productivity.
[0007] An object of the present invention is to provide a copolymer capable of forming a molded product having a high crosslinking rate, excellent productivity, and improved heat aging resistance, small compression set at high and low temperatures, and low-temperature properties (e.g., low-temperature elastic recovery properties, Gehman torsion properties), and a composition containing the copolymer. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by the following configuration, thereby achieving the present invention. A configuration example of the present invention is as follows.
[0009] [1] The polymer has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, The structural unit derived from the non-conjugated polyene [A3] is an ethylene-α-olefin-non-conjugated polyene copolymer (A) containing a structural unit derived from 5-vinyl-2-norbornene:
[0010] [ka]
[0011] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)
[0012] [2] The ethylene / α-olefin / non-conjugated polyene copolymer (A) according to [1], having a Mooney viscosity ML(1+4)100°C of 5 to 60.
[0013] [3] An ethylene / α-olefin / non-conjugated polyene copolymer (A) according to [1] or [2], which satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (mass%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (Pa sec) P〔η * ( ω =0.1) / η * ( ω =100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv) Requirement (7): Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * ( ω =10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * ( ω =0.01)} / Log{η * ( ω =10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -65°C or lower.
[0014] [4] An ethylene copolymer composition comprising: copolymer (A) according to any one of [1] to [3]; and, relative to 100 parts by mass of copolymer (A), 5 to 150 parts by mass of carbon black (B), 0.5 to 7.0 parts by mass of antioxidant (C), and 0.1 to 30 parts by mass of organic peroxide (D).
[0015] [5] The ethylene copolymer composition according to [4], which is a composition for use in a fuel cell gasket.
[0016] [6] A fuel cell gasket obtained by using the ethylene copolymer composition according to [5].
[0017] [7] A molded article formed using the copolymer (A) according to any one of [1] to [3].
[0018] [8] A molded article formed using the ethylene copolymer composition according to [4]. Effect of the Invention
[0019] The ethylene copolymer composition containing the ethylene-α-olefin-non-conjugated polyene copolymer of the present invention has a high crosslinking rate and excellent productivity, and also has excellent heat aging resistance, small compression set at high and low temperatures, and excellent low-temperature properties (e.g., low-temperature elastic recovery properties and Gehman torsion properties), and can be suitably used, for example, for fuel cell gaskets. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] [Ethylene-α-olefin-non-conjugated polyene copolymer (A)] The ethylene-α-olefin-non-conjugated polyene copolymer (A) of the present invention (hereinafter also referred to as "copolymer (A)") has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4). The structural units derived from the α-olefin [A2] having 4 to 20 carbon atoms include a structural unit derived from 1-butene, and the structural units derived from the non-conjugated polyene [A3] include a structural unit derived from 5-vinyl-2-norbornene.
[0021] [ka]
[0022] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. Requirement (2): The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]. Requirement (3): The B value represented by the following formula (i) is 1.20 or more. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)
[0023] Examples of the α-olefins [A2] having 4 to 20 carbon atoms include 1-butene, 1-nonene, 1-decene, 1-nonadecene, 1-eicosene, and the like, which have a linear structure without a side chain; and 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like, which have a side chain. The structural units of the copolymer (A) derived from the α-olefin [A2] having 4 to 20 carbon atoms include structural units derived from 1-butene, and therefore at least 1-butene is used as the α-olefin [A2].
[0024] As the α-olefin [A2], 1-butene may be used alone or in combination of two or more kinds including 1-butene. When the α-olefin [A2] is used in combination with 1-butene, among these, α-olefins having 4 to 10 carbon atoms are preferred, and 1-hexene, 1-octene, etc. are more preferred.
[0025] Ethylene-propylene-non-conjugated polyene copolymers, in which the α-olefin is propylene, have insufficient rubber elasticity at low temperatures, so their applications may be limited. On the other hand, copolymer (A) has structural units derived from α-olefins [A2] with 4 to 20 carbon atoms, so it has excellent rubber elasticity at low temperatures.
[0026] Examples of the non-conjugated polyene [A3] containing two or more partial structures selected from the group consisting of the general formulae (I) and (II) in one molecule include 5-vinyl-2-norbornene (VNB), norbornadiene, 1,4-hexadiene, and dicyclopentadiene. Since the structural units derived from the non-conjugated polyene [A3] of the copolymer (A) include structural units derived from 5-vinyl-2-norbornene (VNB), at least VNB is used as the non-conjugated polyene [A3].
[0027] As the non-conjugated polyene [A3], VNB may be used alone or in combination of two or more kinds including VNB. Among these, it is preferable to use VNB alone since VNB is highly available, crosslinks well with organic peroxides, and improves the heat resistance of the copolymer composition.
[0028] The copolymer (A) may contain, in addition to structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], and the non-conjugated polyene [A3], a structural unit derived from a non-conjugated polyene [A4] containing only one partial structure selected from the group consisting of the general formulae (I) and (II) in one molecule.
[0029] Examples of such non-conjugated polyenes [A4] include 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4-pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(6-heptenyl)-2-norbornene, 5-(3-methyl-5-hexenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(3-ethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like.
[0030] Among these, ENB is preferred because it is easily available, the crosslinking rate during crosslinking with an organic peroxide is easily controlled, and good mechanical properties are easily obtained. The non-conjugated polyene [A4] can be used alone or in combination of two or more kinds.
[0031] Each of the copolymers (A) may contain at least one biomass-derived monomer (ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], a non-conjugated polyene [A3], and a non-conjugated polyene [A4]).
[0032] The copolymer (A) has a Mooney viscosity at 100°C, ML(1+4)100°C, in the range of preferably 5-60, more preferably 20-60, and further preferably 20-50. When the Mooney viscosity ML(1+4)100°C is within the above range, a copolymer having excellent roll processability even in a high hardness oil-less compound, good post-treatment (ribbon handling properties) and excellent rubber physical properties can be obtained.
[0033] Requirement (1) The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The copolymer (A) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.
[0034] The lower limit of the molar ratio [A1] / [A2] is preferably 45 / 55, more preferably 50 / 50, and even more preferably 55 / 45. The upper limit of the molar ratio [A1] / [A2] is preferably 80 / 20, more preferably 75 / 25, and even more preferably 70 / 30.
[0035] Requirement (2) The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % based on the total of the structural unit derived from ethylene [A1], the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms, and the structural unit derived from the non-conjugated polyene [A3] being 100 mol %. The copolymer (A) having this content in the above range has sufficient crosslinkability and flexibility. In this specification, the content of each structural unit in the resin can be measured by NMR spectrum or the like.
[0036] The lower limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 0.2 mol%, more preferably 0.3 mol%. The upper limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 4.0 mol%, more preferably 3.0 mol%, even more preferably 2.0 mol%, particularly preferably 0.7 mol%. When the content of the structural unit derived from the non-conjugated polyene [A3] is within the above range, a copolymer (A) having sufficient crosslinkability, flexibility, and low-temperature properties can be obtained.
[0037] Requirement (3) The B value represented by the following formula (i) is 1.20 or more, preferably 1.20 to 1.80, more preferably 1.22 to 1.60, further preferably 1.24 to 1.50, and particularly preferably in the range of 1.30 to 1.45. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.]
[0038] An ethylene copolymer having a B value below the above range has a large compression set at low temperatures, and it may not be possible to obtain an ethylene copolymer having an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature. The B value is an index showing the randomness of the copolymerization monomer sequence distribution in the copolymer (A), and [E], [X], [Y], and [EX] in the formula (i) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)].
[0039] Requirement (4) The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii). BrNo≧0.5 …Formula (ii) Here, the number of branch points per molecular chain, BrNo, can be determined by a structural analysis method using 3D-GPC. In this specification, specifically, it was determined as described in the examples described later.
[0040] The copolymer (A) more preferably satisfies the following formula (ii-1). BrNo≧0.8 …Formula (ii-1) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii) or (ii-1), because when a crosslinked molded article is produced, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties.
[0041] The copolymer (A) more preferably satisfies the following formula (ii-2). 3.0≧BrNo …Formula (ii-2) It is preferable that the number of branching points per molecular chain satisfies the above formula (ii-2), since the compression set at low temperatures is small and the balance between rubber elasticity at low temperatures and tensile strength at room temperature is excellent.
[0042] The copolymer (A) preferably satisfies any one or more of the following requirements (5) to (8): The copolymer (A) more preferably satisfies any two or more of the requirements (5) to (8), further preferably satisfies any three or more of the requirements (5) to (8), and most preferably satisfies all of the requirements (5) to (8).
[0043] Requirement (5) The weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (mass%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii): 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Here, the weight average molecular weight (Mw) of the copolymer (A) can be determined as a polystyrene-equivalent value measured by gel permeation chromatography (GPC). In this specification, specifically, it is determined by using 3D-GPC as described in the examples described later.
[0044] The copolymer (A) more preferably satisfies the following formula (iii-1). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦60 ...Formula (iii-1) When the "Mw × weight fraction of [A3] / 100 / molecular weight of [A3]" satisfies the formula (iii) or (iii-1), the content of the structural unit derived from the non-conjugated polyene [A3] such as VNB is appropriate, and the degree of crosslinking is appropriate. By using this, the crosslinking speed is excellent, and the molded article after crosslinking has a well-balanced excellent mechanical properties and heat aging resistance.
[0045] Requirement (6) Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (Pa sec) P〔η * ( ω =0.1) / η * ( ω =100)], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv)
[0046] Here, the complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) and the complex viscosity η at frequency ω=100rad / s * ( ω =100) Ratio of P〔η * ( ω =0.1) / η * ( ω =100) ] represents the frequency dependence of viscosity, and corresponds to the left side of the formula (iv) P / ([η] 2.9 ) tends to show high values when there are a lot of long chain branches, although it is affected by factors such as short chain branches and molecular weight.
[0047] Generally, in an ethylene-α-olefin-non-conjugated polyene copolymer, the more structural units derived from non-conjugated polyenes the copolymer contains, the more long chain branches it tends to contain. However, it is considered that copolymer (A) can satisfy the above formula (iv) because it has fewer long chain branches than conventionally known ethylene-α-olefin-non-conjugated polyene copolymers. The copolymer (A) more preferably satisfies the following formula (iv-1). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 5.7 … Formula (iv-1)
[0048] In the present invention, the P value is determined by performing measurements using a viscoelasticity measuring device Ares (manufactured by Rheometric Scientific) at 190° C., strain 1.0%, and various frequencies, and is calculated as the ratio (η * The ratio of
[0049] The intrinsic viscosity [η] of the copolymer (A) in requirement (6) means a value measured in decalin at 135°C. The intrinsic viscosity [η] of the copolymer (A) is preferably 2.5 dl / g or less, more preferably 2.0 dl / g or less, further preferably 1.85 dl / g or less, particularly preferably 1.75 dl / g or less.
[0050] Requirement (7) Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * ( ω =10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * ( ω =0.01)} / Log{η * ( ω =10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v)
[0051] Here, the complex viscosity η * ( ω =0.01) and the complex viscosity η * ( ω =10) is the complex viscosity η in requirement (6) * ( ω =0.1) and the complex viscosity η * ( ω =100) The same procedure is used to calculate the value of the frequency of the measurement. The apparent iodine value derived from the non-conjugated polyene [A3] can be calculated by the following formula: Apparent iodine value derived from [A3] = weight fraction of [A3] × 253.81 / molecular weight of [A3]
[0052] In the formula (v), the left side represents the shear rate dependency which is an index of the amount of long chain branches, and the right side represents an index of the content of the non-conjugated polyene [A3] that is not consumed as long chain branches during polymerization. When the requirement (7) and the formula (v) are satisfied, the degree of long chain branches is not too high, which is preferable. On the other hand, when the formula (v) is not satisfied, it indicates that a large proportion of the copolymerized non-conjugated polyene [A3] is consumed in the formation of long chain branches.
[0053] Requirement (8) The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower, preferably −67° C. or lower, and more preferably −70° C. or lower. When Tg is within the above range, the obtained molded article has excellent low-temperature properties. Specifically, Tg can be determined by the method described in the Examples below.
[0054] <Method for producing copolymer (A)> The copolymer (A) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst that uses a metallocene compound as one component of the catalyst. For example, the examples described in International Publication No. 2015 / 122415, particularly paragraphs
[0249] to
[0320] of the publication, can be adopted as the metallocene catalyst and the production method using the catalyst. Specifically, as described in the examples described later, in the presence of a metallocene catalyst, at least ethylene [A1], an α-olefin [A2] having 4 to 20 carbon atoms, and a non-conjugated polyene [A3] are copolymerized to obtain the copolymer.
[0055] [Ethylene copolymer composition] The ethylene copolymer composition of the present invention (hereinafter also referred to as "the composition") is a composition containing, relative to 100 parts by mass of the copolymer (A), preferably 5 to 150 parts by mass, more preferably 5 to 140 parts by mass, even more preferably 10 to 120 parts by mass, particularly preferably 15 to 100 parts by mass, and most preferably 20 to 80 parts by mass of carbon black (B) (hereinafter also referred to as "component (B)"), preferably 0.5 to 7.0 parts by mass, more preferably 0.5 to 6 parts by mass, even more preferably 1 to 6 parts by mass, particularly preferably 1.5 to 5 parts by mass, and most preferably 2 to 4 parts by mass of an antioxidant (C) (hereinafter also referred to as "component (C)"), and preferably 0.1 to 30 parts by mass, more preferably 0.5 to 25 parts by mass, even more preferably 1 to 20 parts by mass, particularly preferably 1.5 to 10 parts by mass, and most preferably 2 to 5 parts by mass of an organic peroxide (D) (hereinafter also referred to as "component (D)"), relative to 100 parts by mass of the copolymer (A).
[0056] The composition contains, in addition to the copolymer (A), components (B), (C) and (D) in the above-mentioned ranges, and thus has a high vulcanization rate and excellent productivity, as well as excellent heat aging resistance, small compression set at high and low temperatures, and excellent low-temperature properties (e.g., low-temperature elastic recovery (TR) properties and Gehman torsion properties).
[0057] The composition has a Mooney viscosity ML(1+4)100° C. in the range of preferably 1-200, more preferably 30-150, further preferably 50-120, and particularly preferably 70-100. When the Mooney viscosity ML(1+4)100° C. is within the above range, the roll processability is good.
[0058] The composition has a Mooney viscosity ML(1+4)125°C in the range of preferably 1-100, more preferably 20-90, further preferably 30-70, and particularly preferably 40-50. When the Mooney viscosity ML(1+4) 125° C. is within the above range, the roll processability is good.
[0059] <Carbon black (B)> Carbon black (B), one of the components of the present composition, is a type of known rubber reinforcing agent that is compounded in rubber compositions, and is an inorganic substance generally known as carbon black.
[0060] Specific examples of component (B) include SRF, GPF, FEF, MAF, HAF, ISAF, SAF, FT, and MT. The surface of the carbon black may be treated with a silane coupling agent. Commercially available carbon blacks include those under the trade names "Asahi #55G", "Asahi #50HG", "Asahi #60G", "Asahi #60UG", and "Asahi #70" (manufactured by Asahi Carbon Co., Ltd.), and those under the trade names "Seest V" and "Seest SO" (manufactured by Tokai Carbon Co., Ltd.). The component (B) may be used alone or in combination of two or more.
[0061] <Anti-aging agent (C)> The antioxidant (C), which is one of the components of the present composition, is a conventionally known antioxidant, for example, an amine-based antioxidant, a phenol-based antioxidant, or a sulfur-based antioxidant.
[0062] Specific examples of component (C) include aromatic secondary amine antioxidants such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine; phenolic antioxidants such as dibutylhydroxytoluene and tetrakis[methylene(3,5-di-t-butyl-4-hydroxy)hydrocinnamate]methane (trade name "Irganox 1010", manufactured by BASF); bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-methylphenyl]propane; dithiocarbamate-based antioxidants such as nickel dibutyldithiocarbamate; and sulfur-based antioxidants such as 2-mercaptobenzoylimidazole (trade name "Sandant MB", manufactured by Sanshin Chemical Industry Co., Ltd.), 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilauryl thiodipropionate, and distearyl thiodipropionate. The component (C) may be used alone or in combination of two or more.
[0063] <Organic peroxide (D)> The organic peroxide (D), which is one of the components of the composition, is a type of crosslinking agent.Specific examples include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butylperoxybenzoate, ert-butylperoxyisopropylcarbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.
[0064] Of these, organic peroxides such as dicumyl peroxide (DCP), 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and n-butyl-4,4-bis(tert-butylperoxy)valerate are preferred. The component (D) may be used alone or in combination of two or more.
[0065] <Other ingredients> The composition may contain at least one other component depending on the purpose, for example, a polymer other than the copolymer (A), a crosslinking aid, a vulcanization accelerator, a vulcanization aid, a softener, an inorganic filler, a processing aid, an activator, a moisture absorbent, a heat stabilizer, a weather stabilizer, an antistatic agent, a colorant, a lubricant, a thickener, a foaming agent, and a foaming aid. Each additive may be used alone or in combination of two or more.
[0066] <Polymers other than copolymer (A)> The present composition may contain a polymer other than the copolymer (A) (hereinafter also referred to as "other polymer"). Examples of other polymers that require crosslinking include crosslinkable rubbers such as natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber.
[0067] Other polymers that do not require crosslinking include, for example, elastomers such as styrene-butadiene block copolymers (SBS), styrene-based thermoplastic elastomers (TPS) such as polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) and polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), olefin-based thermoplastic elastomers (TPO), vinyl chloride-based elastomers (TPVC), ester-based thermoplastic elastomers (TPC), amide-based thermoplastic elastomers (TPA), urethane-based thermoplastic elastomers (TPU), and other thermoplastic elastomers (TPZ).
[0068] When the other polymer is used, the blending amount of the other polymer in the present composition is usually 100 parts by mass or less, preferably 80 parts by mass or less, per 100 parts by mass of the copolymer (A).
[0069] <Crosslinking aid> When component (D) is used, it is preferable to use a crosslinking aid in combination. Examples of the crosslinking aid include sulfur, quinone dioxime crosslinking aids such as p-quinone dioxime, acrylic crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate, allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate, maleimide crosslinking aids, divinylbenzene, zinc oxide (e.g., ZnO#1 / zinc oxide type 2 (JIS K 1410) (manufactured by Hakusui Tech Co., Ltd.), activated zinc oxide "META-Z102" (manufactured by Inoue Seki Kogyo Co., Ltd.), etc.), and metal oxides such as magnesium oxide.
[0070] When a crosslinking auxiliary is used, the amount of the crosslinking auxiliary in the present composition is usually 0.5 to 10 mol, preferably 0.5 to 7 mol, and more preferably 1 to 6 mol, per mol of component (D).
[0071] <Softener> Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and others, such as microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred.
[0072] When the present composition contains a softener, the blending amount of the softener is usually 100 parts by mass or less, and preferably 80 parts by mass or less, per 100 parts by mass of the copolymer (A).
[0073] <Inorganic fillers> Examples of inorganic fillers include light calcium carbonate, heavy calcium carbonate, talc, and clay. Of these, heavy calcium carbonate such as "Whiten SB" (product name, manufactured by Shiraishi Calcium Co., Ltd.) is preferred.
[0074] When the composition contains an inorganic filler, the amount of the inorganic filler is usually 2 to 50 parts by mass, preferably 5 to 50 parts by mass, based on 100 parts by mass of the copolymer (A). When the amount of the inorganic filler is within the above range, the composition has excellent kneading processability, and a fuel cell gasket having excellent mechanical properties can be obtained.
[0075] <Processing aids> As the processing aid, for example, a wide variety of processing aids that are generally compounded with rubber can be used. Specific examples of processing aids include fatty acids such as ricinoleic acid, stearic acid, palmitic acid, and lauric acid, fatty acid salts such as barium stearate, zinc stearate, and calcium stearate, and esters, etc. Of these, stearic acid is preferred.
[0076] When the present composition contains a processing aid, the amount of the processing aid is usually 10 parts by mass or less, and preferably 8.0 parts by mass or less, per 100 parts by mass of the copolymer (A).
[0077] <Activator> Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.
[0078] When the present composition contains an activator, the amount of the activator is usually 0.2 to 10 parts by mass, and preferably 0.3 to 5 parts by mass, based on 100 parts by mass of the copolymer (A).
[0079] Moisture absorbent Examples of moisture absorbents include calcium oxide, silica gel, sodium sulfate, molecular sieves, zeolite, and white carbon. When the present composition contains a moisture absorbent, the amount of the moisture absorbent is usually 0.5 to 15 parts by mass, and preferably 1.0 to 12 parts by mass, based on 100 parts by mass of the copolymer (A).
[0080] <Foaming Agent> The fuel cell gasket formed using the composition may be either non-foamed or foamed. When the fuel cell gasket is foamed, the composition preferably contains a foaming agent.
[0081] As the foaming agent, any of commercially available foaming agents can be suitably used. Examples of such foaming agents include inorganic foaming agents such as sodium bicarbonate, sodium carbonate, ammonium bicarbonate, ammonium carbonate, and ammonium nitrite; nitroso compounds such as N,N'-dinitrosoterephthalamide and N,N'-dinitrosopentamethylenetetramine; azo compounds such as azodicarbonamide, azobisisobutyronitrile, azocyclohexylnitrile, azodiaminobenzene, and barium azodicarboxylate; sulfonyl hydrazide compounds such as benzenesulfonyl hydrazide, toluenesulfonyl hydrazide, and p,p'-oxybis(benzenesulfonyl hydrazide)diphenylsulfone-3,3'-disulfonyl hydrazide; and azide compounds such as calcium azide, 4,4'-diphenyldisulfonyl azide, and paratoluenemalonyl azide. Among them, azo compounds, sulfonyl hydrazide compounds, and azide compounds are preferably used.
[0082] When the composition contains a foaming agent, the amount of the foaming agent is appropriately selected depending on the performance required for the fuel cell gasket produced from the composition, but the foaming agent is usually used in a ratio of 0.1 to 30 parts by mass, preferably 0.2 to 20 parts by mass, per 100 parts by mass of the copolymer (A).
[0083] <Foaming assistant> If necessary, a foaming assistant may be used together with the foaming agent. The addition of the foaming assistant is effective in adjusting the decomposition temperature of the foaming agent and uniformizing the bubbles. Specific examples of the foaming assistant include organic acids such as salicylic acid, phthalic acid, stearic acid, and oxalic acid, urea, and derivatives thereof.
[0084] When the present composition contains a foaming auxiliary, the foaming auxiliary is usually used in an amount of 1 to 100 parts by mass, preferably 2 to 80 parts by mass, per 100 parts by mass of the foaming agent.
[0085] <Method of manufacturing the present composition> The present composition can be prepared by kneading the copolymer (A), component (B), component (C), and component (D), as well as other components that are blended as necessary, at a desired temperature using a kneading machine such as a mixer, kneader, or roll.
[0086] Specifically, the composition can be prepared by kneading the mixture using a conventional kneading machine such as a mixer or kneader at a predetermined temperature and time, for example, at 80 to 200°C for 3 to 30 minutes, adding other components to the kneaded mixture as needed, and kneading the mixture using a roll at a predetermined temperature and time, for example, at a roll temperature of 30 to 80°C for 1 to 30 minutes.
[0087] <Uses of the composition> The composition is suitable for use in fuel cell gaskets. By using this composition, it is possible to obtain a fuel cell gasket that has superior low-temperature flexibility compared to when conventional EPDM is used, and it is possible to obtain a fuel cell gasket that has superior cold resistance compared to when silicone rubber is used.
[0088] <Fuel cell gasket> The fuel cell gasket of the present invention is formed from the present composition described above. A method for producing a fuel cell gasket from the present composition includes, for example, molding the present composition into the desired shape of a fuel cell gasket and crosslinking the present composition simultaneously with or after this molding.
[0089] Examples of the method for crosslinking include a method in which the present composition is crosslinked by heating it, and a method in which the present composition is crosslinked by irradiating it with an electron beam.
[0090] Specifically, the fuel cell gasket of the present invention can be produced by molding the composition into the intended shape using a molding machine such as an extrusion molding machine, a calendar roll, a press, an injection molding machine, or a transfer molding machine, and crosslinking the composition by heating at 120 to 270°C for 1 to 30 minutes at the same time as molding, or by introducing the molded product into a vulcanization tank and heating the product at 120 to 270°C for 1 to 30 minutes, or by irradiating the product with an electron beam.
[0091] Crosslinking may be performed using a mold or without a mold. When a mold is not used, the molding and crosslinking steps are usually performed continuously. Heating methods in the vulcanization tank can include hot air, glass bead fluidized bed, UHF (ultra-high frequency electromagnetic waves), steam, etc.
[0092] When an electron beam is used as the crosslinking method without using a crosslinking agent, the composition molded into a predetermined shape may be irradiated with an electron beam having an energy of usually 0.1 to 10 MeV, preferably 0.3 to 2 MeV, so that the absorbed dose is usually 0.5 to 35 Mrad, preferably 0.5 to 10 Mrad.
[0093] The fuel cell gasket of the present invention can be preferably used as a fuel cell gasket used in a hydrogen line. In a hydrogen station that supplies hydrogen to fuel cell vehicles (FCVs) and the like, there are many hydrogen lines through which hydrogen passes. The fuel cell gasket of the present invention is used as a fuel cell gasket used in such a hydrogen line.
[0094] At hydrogen stations, hydrogen must be stored in a compressor at high pressure in order to store a large amount of hydrogen. In addition, when hydrogen is supplied from a hydrogen station, it must be sent out at high pressure and high speed, and the temperature of the hydrogen rises during this process. In order to prevent the temperature inside the hydrogen tank of a fuel cell vehicle or the like from rising too high, hydrogen must be stored at low temperatures, for example, at about -40°C at hydrogen stations. For this reason, fuel cell gaskets used in hydrogen lines are required to have sealing properties at low temperatures. The fuel cell gasket of the present invention has both low-temperature properties and mechanical strength (strength and elongation), and can be suitably used in hydrogen lines.
[0095] [Molded body] The molded article of the present invention is formed from the copolymer (A), the crosslinked copolymer (A), or a composition containing the copolymer (A). The obtained molded article (e.g., a crosslinked molded article, a crosslinked foam, etc.) can be used for various applications.
[0096] Specific applications of the molded article of the present invention include tire rubber, O-rings, industrial rolls, packings (e.g., condenser packings), gaskets, belts (e.g., heat insulating belts, copier belts), hoses (e.g., water hoses, brake reservoir hoses, radiator hoses), protective rubber, sponges (e.g., weather strip sponges, heat insulating sponges, protect sponges, microfoam sponges), cables (ignition cables, cab-tire cables, high tension cables), electric wire coating materials (high voltage electric wire coating materials, low voltage electric wire coating materials, marine electric wire coating materials), glass run channels, color skin materials, paper feed rolls, roofing sheets, all-solid-state batteries, and the like.
[0097] As a method for producing the molded article of the present invention, for example, there can be mentioned a method in which copolymer (A) or the present composition (uncrosslinked composition) is molded into a desired shape, and simultaneously with or after this molding, copolymer (A) or the present composition is crosslinked.
[0098] In the molding, the composition is molded into a desired shape using an extruder, a calendar roll, a press molding machine, an injection molding machine, a transfer molding machine, etc. The shape of the molded product may be, for example, a plate shape. EXAMPLES
[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" refers to "parts by mass".
[0100] The physical properties of each copolymer used in the examples and comparative examples were measured as follows. (1) Weight fraction (mass%) and molar ratio The weight fraction (mass%) of each structural unit of the copolymer and the molar ratio of each structural unit are 13 The measured values were obtained by C-NMR. The measured values were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The results were obtained by measuring the C-NMR spectrum.
[0101] (2) Number of branch points BrNo The number of branching points BrNo of the copolymer was calculated by structural analysis from the absolute molecular weight distribution and intrinsic viscosity obtained using a 3D-high temperature GPC device (PL-GPC220 model, Polymer Laboratories). The main measurement conditions are as follows. The dn / dc value required to determine the absolute molecular weight was calculated for each sample from the dn / dc value of standard polystyrene (molecular weight 190,000) of 0.053 and the response intensity of the differential refractometer per unit injected mass. Detector: Differential refractometer / GPC device built-in 2-angle light scattering photometer PD2040 type (manufactured by Precison Detectors) Bridge type viscometer PL-BV400 (Polymer Laboratories) Column: TSKgel GMH HR-H(S)HT x 2 + TSKgel GMH HR -M(S) x 1 (each with inner diameter of 7.8mmφ x length of 300mm, manufactured by Tosoh Corporation) Column temperature: 140℃ Mobile phase: 1,2,4-trichlorobenzene (containing 0.025% BHT) ·Injection volume: 0.5mL Sample concentration: ca 1.0mg / mL Sample filtration: Filtration through a sintered filter with a pore size of 1.0 μm
[0102] From the relationship between the intrinsic viscosity obtained from the viscometer and the absolute molecular weight obtained from the light scattering photometer, the long chain branching parameter g'i for each eluted component was calculated from the following formula (v-1).
[0103]
number
[0104] Here, [η] = KM v The equation was applied: v = 0.725. This equation is called the Mark-Houwink-Sakurada equation, where K is the solvent constant and M is the average molecular weight. Further, the average values of g' were calculated from the following formulas (v-2), (v-3), and (v-4). Note that a trendline assuming the presence of only short chain branches was determined for each sample.
[0105]
number
[0106] Furthermore, the number of branch points per molecular chain, BrNo, was calculated using g'w. BrNo was calculated using the following Zimm-Stockmayer formula (v-5). Here, g is the long chain branching parameter calculated from the radius of gyration Rg, and the following simple correlation is made between g' calculated from the intrinsic viscosity: g=g' (1 / ε ) (ε(structure factor)=0.5~1.5) Various values have been proposed for ε in the formula depending on the shape of the molecule. Here, the calculation was performed assuming ε = 1 (i.e. g' = g).
[0107]
number
[0108] (3) Intrinsic viscosity [η] The intrinsic viscosity [η] (dl / g) of the copolymer was measured using a fully automatic intrinsic viscometer manufactured by Rigo Co., Ltd. at a temperature of 135° C. and in decalin as a measurement solvent.
[0109] (4) Weight average molecular weight (Mw) The weight average molecular weight (Mw) of the copolymer was determined using a 3D-high temperature GPC apparatus (PL-GPC220, manufactured by Polymer Laboratories) under the same measurement conditions as in (2) above.
[0110] (5) Mooney viscosity The Mooney viscosity ML(1+4)100° C. of the copolymer was measured using a Mooney viscometer (SMV-301 model, manufactured by Shimadzu Corporation) in accordance with JIS K 6300 (1994).
[0111] (6) Complex viscosity η * and P value The rheometer used was the Ares viscoelasticity measuring device (manufactured by Rheometric Scientific), and the complex viscosity η at a frequency of ω = 0.01 rad / s was measured under the conditions of 190°C and 1.0% strain. * ( ω =0.01) , complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) , complex viscosity η at frequency ω=10rad / s * ( ω =10) and the complex viscosity η at frequency ω = 100 rad / s * ( ω =100) (All units are Pa·sec.)
[0112] In addition, the obtained results show that η * ( ω =0.1) and η * ( ω =100) The P value (η * ( ω =0.1) / η * ( ω =100) ) was calculated.
[0113] (7) Glass transition temperature (Tg) The glass transition temperature (Tg) of the copolymer was determined by DSC measurement under the following conditions. Using a differential scanning calorimeter (RDC220, manufactured by SII), approximately 10 mg of a sample was heated from 30°C to 200°C at a heating rate of 50°C / min in a nitrogen atmosphere and held at that temperature for 10 minutes. It was then cooled to -100°C at a heating rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a heating rate of 10°C / min.
[0114] The glass transition temperature (Tg) is detected as the DSC curve bending due to the change in specific heat during the second heating, and the baseline shifts in parallel. The glass transition temperature (Tg) is determined as the temperature at the intersection of the tangent to the baseline lower than this bending and the tangent to the point where the slope of the bending part is maximum.
[0115] [Ethylene-α-olefin-non-conjugated polyene copolymer (A)] In the following Examples 2-1 to 2-3, the copolymers (A-1) to (A-3) obtained in the following Examples 1-1 to 1-3 were used as the copolymer (A).
[0116] [Example 1-1] A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 41.4 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 3.2 kg / h, the 1-butene feed rate was 13.5 kg / h, the VNB feed rate was 290 g / h, and the hydrogen feed rate was 2 NL / h.
[0117] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.0026 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.013 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 20 mmol / h as an organoaluminum compound.
[0118] In this way, a solution containing 22% by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for 24 hours.
[0119] By the above operations, ethylene-1-butene-VNB copolymer (A-1) was obtained at a rate of 6.0 kg per hour. The physical properties of the obtained copolymer (A-1) were measured by the methods described above. The results are shown in Table 1.
[0120] [Example 1-2] A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 30.5 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 5.3 kg / h, the 1-butene feed rate was 21.5 kg / h, the VNB feed rate was 566 g / h, and the hydrogen feed rate was 10 NL / h.
[0121] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.00903 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.045 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 30 mmol / h as an organoaluminum compound.
[0122] In this way, a solution containing 20% by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for a whole day and night.
[0123] By the above operations, ethylene-1-butene-VNB copolymer (A-2) was obtained at a rate of 8.5 kg per hour. The physical properties of the obtained copolymer (A-2) were measured by the method described above. The results are shown in Table 1.
[0124] [Examples 1-3] A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 32.4 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 5.2 kg / h, the 1-butene feed rate was 24.0 kg / h, the VNB feed rate was 1070 g / h, and the hydrogen feed rate was 17 NL / h.
[0125] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.0154 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.077 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 30 mmol / h as an organoaluminum compound.
[0126] In this way, a solution containing 20% by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for a whole day and night.
[0127] By the above operations, ethylene-1-butene-VNB copolymer (A-3) was obtained at a rate of 7.2 kg per hour. The physical properties of the obtained copolymer (A-3) were measured by the methods described above. The results are shown in Table 1.
[0128] [Ethylene-1-butene-ENB copolymer (E-1)] In the following Comparative Example 2-1, the copolymer (E-1) obtained in the following Comparative Example 1-1 was used. [Comparative Example 1-1] According to the description of [Synthesis Example C1] of WO 2015 / 122415, an ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer (E-1) having the following physical properties was obtained. The physical properties of the obtained copolymer (E-1) were measured by the method described above. The results are shown in Table 1.
[0129] [Table 1]
[0130] [Example 2-1] <<Preparation of Ethylene Copolymer Composition>> Using a MIXTRON BB MIXER (manufactured by Kobe Steel, Ltd., BB-4 type, volume 2.95 L, rotor 4WH), 100 parts by mass of copolymer (A-1), 5 parts by mass of activated zinc oxide (trade name: META-Z102, manufactured by Inoue Lime Industrial Co., Ltd.) as a crosslinking aid, 1 part by mass of stearic acid, 46 parts by mass of Asahi #60UG (manufactured by Asahi Carbon Co., Ltd., grade: FEF) as carbon black (B), 2 parts by mass of 2-mercaptobenzimidazole (trade name: Sandant MB, manufactured by Sanshin Chemical Industry Co., Ltd.) as an antiaging agent (C), and 2 parts by mass of dibutylhydroxytoluene, tetrakis [methylene (3,5-di-t-butyl-4-hydroxy) hydrocinnamate] methane (trade name: Irganox 1010, manufactured by BASF) as an antiaging agent (C) were mixed in amounts and kneaded to obtain compound 1.
[0131] The kneading conditions were rotor speed of 50 rpm and floating weight pressure of 3 kg / cm 2 The kneading time was 5 minutes, and the kneading discharge temperature was 150°C. Next, after confirming that the temperature of Compound 1 had reached 40°C, 6.8 parts by mass of dicumyl peroxide (DCP) (40% masterbatch, product name: Percumyl D-40, manufactured by Nippon Oil & Fats Co., Ltd.) was added as an organic peroxide (D) to Compound 1 using a 6-inch roll and kneaded to obtain Compound 2.
[0132] The kneading conditions were roll temperature front roll / rear roll = 50°C / 50°C, roll peripheral speed front roll / rear roll = 18 rpm / 15 rpm, roll gap 3 mm, and kneading time 5 minutes to obtain compound 2.
[0133] <Evaluation of physical properties of uncrosslinked rubber> [Physical property test 1: Mooney viscosity] The Mooney viscosity ML(1+4)100°C of Blend 2 (compound) was measured using a Mooney viscometer (SMV-301 model, manufactured by Shimadzu Corporation) in accordance with JIS K 6300 (1994).
[0134] [Physical property test 2: Evaluation of crosslinking (vulcanization) characteristics] The crosslinking rate tC90 of Compound 2 was measured using a vulcanization measuring device: MDR2000 (manufactured by ALPHA TECHNOLOGIES) as follows. The torque change obtained under conditions of constant temperature and constant shear rate was measured. The difference S'Max-Min between the maximum torque S'Max (dNm) and the minimum torque S'Min (dNm), the time tC90 (min) when the torque of the measured sample reached 90%, and the MCR (dNm / min) were calculated, assuming the minimum torque S'Min to be 0% and the maximum torque S'Max to be 100%. The measurement conditions were a temperature of 180°C and a time of 15 minutes. The smaller this tC90, the faster the vulcanization speed (crosslinking speed).
[0135] Evaluation of physical properties of vulcanized (crosslinked) products Compound 2 was crosslinked for 10 minutes at 180° C. using a press molding machine to prepare a sheet (vulcanized product (crosslinked product)) having a thickness of 2 mm. The obtained sheet was subjected to a hardness test, a tensile test, a Gehman torsion test, a heat aging test, and a TR test by the following methods.
[0136] Compound 2 was vulcanized at 180°C for 13 minutes using a press molding machine equipped with a cylindrical mold to prepare a right cylindrical test piece with a thickness of 12.7 mm and a diameter of 29 mm, and a test piece (vulcanizate) for compression set (CS) testing was obtained. The compression set (CS) test specimens thus obtained were used to evaluate the compression set by the following method. The results are shown in Table 2.
[0137] [Compression set (CS) test: Compression set] The compression set (CS) measurement specimens were subjected to measurements of compression set after treatment at 150° C. for 22 hours, at 23° C. for 22 hours, and at −40° C. for 22 hours in accordance with JIS K 6262 (1997).
[0138] [Hardness test: Hardness (Durometer-A (shore-A))] The hardness of the sheet was measured in accordance with the description of "Hardness test" in Section 7 of JIS K 7312 (1996) "Physical test methods for thermosetting polyurethane elastomer moldings" and the description of Test Type A in Section 6 of JIS K 6253 (2006) "Vulcanized rubber and thermoplastic rubber - Determination of hardness".
[0139] [Tensile test: modulus, tensile stress at break, tensile elongation at break] The modulus, tensile stress at break, and tensile elongation at break of the sheet were measured by the following methods. The sheet was punched out to prepare a No. 3 dumbbell test piece described in JIS K 6251 (1993). Using this test piece, a tensile test was performed according to the method specified in JIS K 6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the tensile stress when the elongation rate was 25% (25% modulus (M25)), the tensile stress when the elongation rate was 50% (50% modulus (M50)), the tensile stress when the elongation rate was 100% (100% modulus (M100)), the tensile stress at break (TB), and the tensile elongation at break (EB) were measured.
[0140] [Gehman Torsion Test: Temperature Dependence of Torsional Rigidity] The sheet is punched out and the torsional rigidity is measured in accordance with JIS K 6261-3. 10 (℃) was calculated.
[0141] [Heat aging test] The sheet was subjected to a heat aging test at 180° C. for 72 hours and 168 hours according to JIS K 6257. The hardness, tensile stress at break, and tensile elongation at break of the sheet after the heat aging test were measured in the same manner as in the above items [Hardness (Durometer-A)] and [Modulus, tensile stress at break, and tensile elongation at break].
[0142] AH (shore-A) was calculated from the difference in hardness before and after the heat aging test, and the rate of change after the test from the values before the heat aging test to the values before the test was calculated as Ac(TB) and Ac(EB), respectively, from the tensile stress at break (TB) and tensile elongation at break (EB) before and after the heat aging test.
[0143] [TR test (low-temperature elastic recovery test)] The sheet was subjected to a TR test (low temperature elastic recovery test) in accordance with JIS K 6261-4 to measure cold resistance. In this test, the stretched sheet is frozen and the temperature is continuously raised to measure the recovery of the stretched sheet. The temperatures at which the length of the test piece shrinks (recovers) by 10% and 70% due to heating are indicated as TR10 and TR70, respectively. The lower the TR10 (unit: °C), the better the cold resistance.
[0144] [Comparative Example 2-1] The same procedure as in Example 1 was carried out, except that the copolymer (E-1) was used instead of the copolymer (A-1) used in Example 1. The results are shown in Table 2.
[0145] [Examples 2-2, 2-3, and Comparative Example 2-2] Instead of the copolymer (A-1) used in Example 2-1, the copolymer (A-2), copolymer (A-3), or copolymer (E-1) was used to obtain ethylene copolymer compositions (compounds 1 and 2) in the amounts shown in Table 2, and various physical properties were measured by the method described in Example 2-1. The Mooney viscosity of the compound 2 was measured at ML(1+4) 125°C, and in the compression set (CS) test, a test piece (vulcanized product) vulcanized at 180°C for 15 minutes was used to measure the compression set after treatment at 150°C x 72 hours, 23°C x 22 hours, and -40°C x 22 hours, and in the heat aging test, a heat aging test was performed at 180°C for 168 hours and 336 hours. The results are shown in Table 2.
[0146] [Table 2]
[0147] As shown in Table 2, the compositions (Examples 2-1 to 2-3) containing 100 parts by mass each of copolymers (A-1) to (A-3) had a faster vulcanization rate and better productivity than the compositions (Comparative Examples 2-1 and 2-2) containing 100 parts by mass of copolymer (E-1). In addition, they had smaller heat aging resistance and compression set at high and low temperatures, and were excellent in low-temperature properties (e.g., low-temperature elastic recovery (TR) properties and Gehman torsion properties).
Claims
1. The polymer has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, An ethylene / α-olefin / non-conjugated polyene copolymer (A), in which the structural unit derived from the non-conjugated polyene [A3] contains a structural unit derived from 5-vinyl-2-norbornene: 【Chemistry 1】 Requirement (1): the molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2] and a non-conjugated polyene [A3], and [EX] represents the ethylene [A1]-α-olefin having 4 to 20 carbon atoms [A2] dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC, satisfies the following formula (ii): BrNo≧0.5...Formula (ii)
2. The ethylene / α-olefin / non-conjugated polyene copolymer (A) according to claim 1, having a Mooney viscosity ML(1+4) 100° C. of 5 to 60.
3. The ethylene / α-olefin / non-conjugated polyene copolymer (A) according to claim 1, which satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (mass%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at a frequency ω = 0.1 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * ( ω =0.1) (Pa sec) and the complex viscosity η at a frequency ω = 100 rad / s * ( ω =100) (Pa sec) P [η * ( ω =0.1) / * ( ω =100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of the [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ weight fraction of [A3] × 6 ... formula (iv) Requirement (7): Complex viscosity η at a frequency ω = 0.01 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * ( ω =0.01) (Pa sec) and the complex viscosity η at a frequency ω = 10 rad / s * ( ω =10) (Pa·sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * ( ω =0.01) } / Log{η * ( ω =10) }≦0.0753×{apparent iodine value derived from the non-conjugated polyene [A3]}+1.42 ... formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower.
4. An ethylene copolymer composition comprising the copolymer (A) according to any one of claims 1 to 3, and 5 to 150 parts by mass of carbon black (B), 0.5 to 7.0 parts by mass of an antioxidant (C), and 0.1 to 30 parts by mass of an organic peroxide (D) relative to 100 parts by mass of the copolymer (A).
5. The ethylene copolymer composition according to claim 4, which is a fuel cell gasket composition.
6. A fuel cell gasket obtained by using the ethylene copolymer composition according to claim 5.
7. A molded article formed using the copolymer (A) according to any one of claims 1 to 3.
8. A molded article formed using the ethylene copolymer composition according to claim 4.
Citation Information
Patent Citations
Composition for seal packing and use thereof
JP2017075293A
ETHYLENE / $g(a)-OLEFIN / UNCONJUGATED POLYENE COPOLYMER RUBBER, RUBBER COMPOSITION FOR SEALING, MOLDED RUBBER FOR SEALING, AND PROCESS FOR PRODUCING THE MOLDED RUBBER
WO2000059962A1
Cited By
Rubber composition for the rubber layer used in the rubber layer of a laminated hose for hydrogen transfer, and laminated hose for hydrogen transfer
JP7906936B1